Prosociality of Modernist Islamic Volunteers in Responding to The Semeru Volcano Eruption - Hazim, Hazim; Wardati, Maryam Effy; Ulfah, Tri Megawati (Universitas Islam Negeri Madura, 2023)
Recently, there has been growing interest in the study of community responses to disasters in Indonesia at macro and meso-levels analysis while little has been paid attention to this study at the micro one or individual level. To fill the literature gap, this article aims to describe prosocial behaviors performed by volunteers involved in addressing the Semeru volcano eruption victims in Lumajang Indonesia occurred in 2021. It was a result of descriptive quantitative research involving 202 participants who identified themselves as Muhammadiyah’s volunteers involved in the humanitarian activities in addressing the natural disaster. The data collection of pro-sociality utilized a prosocial behaviors scale including five aspects: honesty, helping, cooperating, caring, and donating. The validity test of the items used corrected item-total correlation that resulted in 34 valid items, and it had a good reliability based on Cronbach’s coefficient alpha test which was 0,953. The result shows that the participants had predominantly at the moderate level of prosocial behaviors which was four-fifths of the participants. Only a small proportion placed at the high pro-sociality, likewise those who were at the low level meaning these two categories were not significant. This finding is expected to enrich literature related to the role of civil society in responding to disasters, especially at the individual level. However, some relevant topics such as relating prosocial acts to other variables need to get attention for future research to result in comprehensive empirical evidence on this issue.